Audit and feedback strategies: study protocol and preliminary results from the EASY-NET project. (20th October 2021) - Agabiti, N; Grilli, R; Valent, F; Ciccone, G; Marchesini Reggiani, G; Marenzi, G; Di Carlo, C; Bramanti, P; Davoli, M
Abstract: Background: In Italy there is evidence of a large variability in health care services and health outcomes. This multi-regional project is funded on Ministry of Health and Health Regional Authorities (code NET-2016-02364191). The aims are: 1) To test the effectiveness of Audit and Feedback (A&F) interventions in improving health professional practices and patients' outcomes in different settings using both a quantitative and a qualitative approach. 2) To examine factors that may explain variations in the effectiveness of A&F. 3) To evaluate the impact of A&F in reducing avoidable differences in access to effective health care interventions in socioeconomically disadvantaged populations. Methods: In the 7 participating Regions (about 33 million inhabitants) experimental study designs have been implemented in different clinical areas (e.g. before-after controlled study, cluster randomized trial): in Lazio emergency care and chronic diseases care, in Friuli Venezia Giulia emergency care, in Piemonte oncology care, in Emilia Romagna chronic disease care, in Lombardia cardiovascular care, in Calabria deliveries and maternal health, in Sicilia emergency care. The effectiveness of different types of A&F are compared in term of outcomes using health information system databases. Results: Preliminary results show large heterogeneity in developing and conducting A&F, in term of team project composition, type of intervention, clinicians' behavior to be changed, outcomes indicators, professionals involved, structure and timing of data reporting, actions to be implemented after the intervention. Limited awareness and interest of clinicians in A&F interventions was found. Conclusions: The project represents a unique opportunity to explore how A&F interventions could be better designed. Different A&F strategies will be compared in term of clinical outcomes. The identification of barriers/facilitating factors will supply knowledge on mechanisms and tools to enhance A&F effectiveness. Key messages: The project supports providers in reducing gap between knowledge and practice. The project promotes culture of interprofessional collaboration as a key point for high quality care.